DEVELOPING A FUNCTIONAL DEFINITION OF SMALL-SCALE FISHERIES IN SUPPORT OF MARINE CAPTURE FISHERIES MANAGEMENT IN INDONESIA - Abdul Halim; Budy Wiryawan; Neil R. Loneragan; Adrian Hordyk; M. Fedi A. Sondita; Alan T. White; Sonny Koeshendrajana; Toni Ruchimat; Robert S. Pomeroy; Christiana Yuni (JFMR (Journal of Fisheries and Marine Research), 2020)
Small-scale capture ﬁsheries have a very important place globally, but unfortunately are still mostly unregulated. Typically, they are deﬁned based on capture ﬁsheries characteristics, technical attributes of ﬁshing vessels, and socio-economic attributes of ﬁshers. Indonesia uses the term ‘small-scale ﬁsher’ (nelayan kecil), currently deﬁned to include ﬁshing boats of ≤ 10 gross tons (GT), which previously covered only boats of ≤ 5 GT. Because small-scale ﬁshers are by law granted a privilege by government to be exempted from ﬁsheries management measures (e.g. ﬁsheries licensing system), its current deﬁnition jeopardizes ﬁsheries sustainability and signiﬁcantly increases the size of unregulated and unreported ﬁsheries. It is also unfair, as it legitimizes the payment of government support to relatively well-oﬀ ﬁshers. This paper aims to develop a functional deﬁnition of small-scale ﬁsheries (perikanan skala kecil) to guide policy implementation to improve capture ﬁsheries management in Indonesia. A deﬁnition of small-scale ﬁsheries is proposed as a ﬁsheries operation, managed at the household level, ﬁshing with or without a ﬁshing boat of < 5 GT, and using ﬁshing gear that is operated by manpower alone. This deﬁnition combines attributes of the ﬁshing vessel (GT), the ﬁshing gear (mechanization), and the unit of business decision making (household) to minimize unregulated and unreported ﬁshing and focus government aid on people who are truly poor and vulnerable to social and economic shocks. The terms small-scale ﬁsheries and small-scale ﬁshers must be legally diﬀerentiated as the former relates to ﬁsheries management and the latter relates to empowerment of marginalized ﬁshers.